Quick Preparative Separation of Natural Naphthopyranones with Antioxidant Activity by High-Speed Counter-Current Chromatography - Gilda Guimarães Leitão; Suzana Guimarães Leitão; Wagner Vilegas (2002)
The natural naphthopyranones paepalantine (1), paepalantine-9O-β-ᴅ-glucopyranoside (2) and paepalantine-9-O-β-ᴅ-allopyranosyl-(1→6)-O-β-ᴅ-glucopyranoside (3) were separated in a preparative scale from the ethanolic extract of the capitula of Paepalanthus bromelioides by high-speed counter-current chromatography (HSCCC). The solvent system used was composed of water-ethanol-ethyl acetate-hexane (10:4 : 10:4, v/v/v/v). This technique led to the separation of the three different naphthopyranone glycosides in pure form in approximately 7 hours. Paepalantine showed a good antioxidant activity when assayed by the DPPH radical spectrophotometric assay.